The Value of Better Weather Information to the Raisin Industry - Lave, Lester B. (Econometrica, 1963)
This report utilizes decision theory to investigate the possible benefits of better weather information to California raisin growers. A supply curve is fitted to the raisin industry and used to evaluate the importance of various factors: weather is of overwhelming importance. Subsequent analysis focuses on the most vulnerable aspect of raisin production: its dependence on early forecasts of rain in September and October when the grapes are being dried and in danger of being damaged by rain. Section 1, in the tradition of micro-economic, partial equilibrium analysis, is concerned with the value of weather information to a single grower. Only the grower focused upon is assumed to receive the better information. This assumption implies there is high value for forecasting rain three weeks in advance. A figure of 90.95 per acre is the value of perfect three week forecasts. Were this value to be realized for each bearing acre in 1960, the total value of better weather information to the raisin industry would be 20,300,000. But merely summing across firms to get industry totals may lead to a fallacy of composition: the analysis must be extended to a wider partial equilibrium framework. Section 2 examines the value of better weather information to the raisin industry as a whole. Since costs are not greatly affected by improved weather information, profit differences are closely approximated by changes in revenue. The elasticity of demand for raisins is calculated from a demand curve fitted to industry data. The inelasticity of demand causes profit to fall under the impact of better information, at least in the short run. The scope of the analysis is then extended to other industries. Using this wider viewpoint, the Conclusion examines the possibility of a simple tax that would reallocate land and labor. The presence of released resources seems to imply a clear gain for better information. However, the basis of such a gain is positive value for these resources in other uses. But the short run inelasticity of other possible products makes it clear that, at least in the short run, better weather information results in net loss. However, some relief is offered through the possibility of regulation. An Appendix examines the question of the value of inaccurate forecasts.